1994
DOI: 10.1002/anie.199413941
|View full text |Cite
|
Sign up to set email alerts
|

New Cyclic Derivatives of 3′‐Amino‐3′‐deoxy‐adenosine‐5′‐diphosphate, ‐triphosphate, and ‐methylenebis(phosphonate)

Abstract: COMMUNICATIONS tone enolates to x,P-unsaturated aldehydes. The present carbene route offers an attractive alternative to this otherwise generally difficult 231 Exper imen tal Pro cediire lob: To a cooled ( -80 C ) solution o f 3 b (1.44 g, 2.68 mmol) in T H F (30 niL) was added a 2.5 M solution of BuLi in hexane (1.15 mL. 2.8 mmol) under nitrogen and the mixture was stirred at -80 C for 1 h and between -80 -C and room temperature for 0.5 h. After ieinoval of the solvents in vacuo : I solution of NaOMe (ca. 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Most nucleoside diphosphates were purchased from Sigma. AZT-DP and 3‘-amino-3‘-deoxyADP were obtained as previously described ( , ). 3‘-deoxyADP was prepared by chemical phosphorylation of the nucleoside.…”
Section: Methodsmentioning
confidence: 99%
“…Most nucleoside diphosphates were purchased from Sigma. AZT-DP and 3‘-amino-3‘-deoxyADP were obtained as previously described ( , ). 3‘-deoxyADP was prepared by chemical phosphorylation of the nucleoside.…”
Section: Methodsmentioning
confidence: 99%
“…Pankiewicz et al suggest an interesting process with nucleoside bicyclic trisanhydrides found in the reaction between nucleoside 5‘-methylenediphosphonates and DCC. Thus, the reaction of the trisanhydride derivative of 2‘,3‘- O -isopropylideneadenosin-5‘-yl with 2‘,3‘- O -isopropylidenetiazofurin leads to the β-methylene-TAD in 92% overall yield 10a. The method has been recently used in the synthesis of MAD 6a.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, only the synthesis of nucleoside methylenediphosphonate sugars or dinucleoside methylenediphosphonates is documented. , As part of our program in the synthesis of analogues of natural glycosyl-disubstituted pyrophosphates, we have recently described preliminary results on the one-pot alkylidene diphosphorylation of 2,3- O -isopropylidene uridine or 2,3:5,6-di- O -isopropylidene- d -mannofuranose to synthesize the methylenediphosphonate analogues of natural P 1 , P 2 -glycosyl-disubstituted pyrophosphates …”
Section: Introductionmentioning
confidence: 99%
“…To form the P-N linkage, we chose EDC-promoted coupling of 2 with C-ethyl protected l-amino acids (Val, Leu, or Phe) in aqueous solution under neutral to slightly alkaline conditions. 25 The intermediate 2 was obtained by quantitative and regioselective silyldealkylation of the P,P-dimethyl groups of trimethyl PFA with bromotrimethylsilane (BTMS). 26,27 The amidation reaction was followed by 31 P NMR, which revealed replacement over several hours of the singlet resonance of 2 by a doublet due to CH-N-P coupling.…”
mentioning
confidence: 99%